Combined lesion of endodont and periodontal in adults and its causes - P. V. Moroz; A. K. Iordishvili (Эндодонтия Today)
Aim. To date, specialists have not studied issues related to the formation and progression of endodontoparodontal lesions. Purpose is to determine the main causes of combined lesions of endodont and periodontal in adults.Material and methods. A clinical study was conducted on 175 patients with chronic periodontitis and chronic generalized periodontitis. In the comparison group, 79 patients with chronic generalized periodontitis were combined. The main causes of the occurrence of combined lesions of the endodont and periodontal in adults with the use of clinical paraclinical, functional, including the study of periodontal microcirculation, and statistical research methods are identified.Results. The main predisposing factors of combined damage to endodontal and periodontal tissues have been established, to which periodontal pockets with a depth of more than 5 mm should be attributed, chronic periapical processes of the teeth with severe inflammatory resorption of bone tissue, the foci of which relate to granulating periodontitis, exceed 7 mm in diameter and are accompanied by a decrease in hemomicrocirculation. periodontal tissue. The main causes of the occurrence of combined endodontal and periodontal lesions in adults are identified, and the main predisposing factors of combined endodontal and periodontal tissue lesions are established, which should be taken into account in clinical practice of dentists.